VD_FINDINFO HC / 2016 / 5 vom 20. November 2015 - VD Tribunal cantonal (2015)
VENTE, VOLONTÉ RÉELLE, INTERPRÉTATIONSENS GÉNÉRAL, LÉGITIMATION ACTIVE ET PASSIVE, NULLITÉ, ERREUR ESSENTIELLE, DOLVICE DU CONSENTEMENT | 164 al. 1 CO, 18 CO, 23 CO, 28 CO